Effect of Sugarcane Varieties and Milling Delay Time on Cane Sugar Yield - Muhtadi, Much Misbah; Sitawati, Sitawati; Suryanto, Agus (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The quality of sugarcane decreases after harvesting so that it affects the yield and sugar production. The objective of this study was to determine the decline in sugarcane production and sugar yield in different varieties and milling delay time. This study used a split plot design consisting of three varieties (PS 881; PSJK 922; Bululawang) as the main plot and delay time (0; 2; 4 days) as sub plots with three replications so that 27 experimental units need to be provided. The observation parameters consisted of initial stalk weight, stalk weight after delay time, initial yield per hectare, yield per hectare after delay time, ºbrix, %pol, purity, cane yield and sugar yield. Results show that variety and delay time had an effect on stalk weight loss, juice quality, cane and sugar yield. PS 881 and PSJK 922 varieties showed better juice quality and higher cane and sugar yield compared to Bululawang varieties. Sugarcane with a delay time of up to 4 days showed lower stalk weight, juice quality, cane and sugar yield as compared to no delay time. The loss of stalk weight and yield of sugarcane at 2 days delaying time can reach 9.2% and 12.3% at 4 days delay time. Keywords: Delaying time, Juice quality, Sugarcane, Varieties.